High throughput analysis of MHC‐I and MHC‐DR diversity of Brazilian cattle populations. (17th June 2021) - Vasoya, Deepali; Oliveira, Priscila Silva; Muriel, Laura Agundez; Tzelos, Thomas; Vrettou, Christina; Morrison, W. Ivan; de Miranda Santos, Isabel Kinney Ferreira; Connelley, Timothy
Abstract : The major histocompatibility complex (MHC) contains many genes that play key roles in initiating and regulating immune responses. This includes the polymorphic MHCI and MHCII genes that present epitopes to CD8+ and CD4+ T‐cells, respectively. Consequently, the characterisation of the repertoire of MHC genes is an important component of improving our understanding of the genetic variation that determines the outcomes of immune responses. In cattle, MHC (BoLA) research has predominantly focused on Holstein‐Friesian animals (as the most economically important breed globally), although the development of high‐throughput approaches has allowed the BoLA‐DRB3 repertoire to be studied in a greater variety of breeds. In a previous study we reported on the development of a MiSeq‐based method to enable high‐throughput and high‐resolution analysis of bovine MHCI repertoires. Herein, we report on the expansion of this methodology to incorporate analysis of the BoLA‐DRB3 and its application to analyse MHC diversity in a large cohort of cattle from Brazil (>500 animals), including representatives from the three major Bos indicus breeds present in Brazil – Guzerat, Gir and Nelore. This large‐scale description of paired MHCI‐DRB3 repertoires in Bos indicus cattle has identified a small number of novel DRB3 alleles, a large number of novel MHCI alleles and haplotypes, and provided novel insights into MHCI‐MHCII association ‐ further expanding our knowledge of bovine MHC diversity.